Gauge theory of elementary particle physics - Cheng, Ta-Pei (Oxford University Press, 1982)
This is a practical introduction to the principal ideas in gauge theory and their applications to elementary particle physics. It explains technique and methodology with simple exposition backed up by many illustrative examples. Derivations, some of well known results, are presented in sufficient detail to make the text accessible to readers entering the field for the first time. The book focuses on the strong interaction theory of quantum chromodynamics and the electroweak interaction theory of Glashow, Weinberg, and Salam, as well as the grand unification theory, exemplified by the simplest SU(5) model. Not intended as an exhaustive survey, the book nevertheless provides the general background necessary for a serious student who wishes to specialize in the field of elementary particle theory. Physicists with an interest in general aspects of gauge theory will also find the book highly useful